1984
DOI: 10.1139/v84-301
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic diazo compounds. XIV. The synthesis of 7-substituted 3-diazo-2-norbornanones and the infrared and proton and carbon-13 nuclear magnetic resonance spectra of these diazo ketones and their precursors

Abstract: . 62, 1751 (1984).syn-and anti-7-lsopropyl-2-norbornanone (5 and 6) were prepared by catalytic hydrogenation of 7-isopropylidene-2-norbornanone; syri-and anti-7-benzhydryl-2-norbornane (9 and 10) were prepared in analogous fashion. Kctones 5 and 6 and syrl-and arlti-7-tert-butyl-2-norbornanone (7 and 8) were converted to the corresponding 3-diazo-2-norbornanones 1-4 via the monotosylhydrazones 44-47 of the corresponding a-diketones 40-43. The 'H and "C nmr spcctra of 1-10,40-47, and thcir precursors have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This compared well with the literature values. [26][27][28] The use of ZnI 2 29 or in situ generated Cu(I) as catalysts gave similar yields and the same exo/endo selectivity, consistent with previous studies. 30,6 When the chloronitrile 3 exo/endo mixture was subjected to aqueous basic conditions, the endo-CN isomer of 3 reacted more quickly to afford the corresponding endo a-chloro amide than did the exo-CN isomer.…”
Section: Introductionsupporting
confidence: 83%
“…This compared well with the literature values. [26][27][28] The use of ZnI 2 29 or in situ generated Cu(I) as catalysts gave similar yields and the same exo/endo selectivity, consistent with previous studies. 30,6 When the chloronitrile 3 exo/endo mixture was subjected to aqueous basic conditions, the endo-CN isomer of 3 reacted more quickly to afford the corresponding endo a-chloro amide than did the exo-CN isomer.…”
Section: Introductionsupporting
confidence: 83%
“…We found that 5 mol % of complex 5a would catalyze the reaction shown to give high conversion to 9a and 9b as a 7:1 mixture of endo and exo isomers (Scheme ). NMR spectroscopy reveals that the endo-2-chloro isomer is favored (as is the case with the uncatalyzed reaction (4:1 mixture) 11c. The enantioselectivity of the process could be estimated by GC 12 and was always found to be low (ca.…”
Section: Resultsmentioning
confidence: 94%
“…An enantioselective version of the Diels−Alder reaction of acrylonitrile derivatives would be a very useful process, as the nitrile group is readily transformed into other functionalities. In the case of substrate 7 , the cyano and chloro groups can be simply converted to a carbonyl group, and it therefore acts as a useful ketene equivalent …”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of 7,7-Dichloro-4-isopropylidene-bicyclo[3.2.0]-hept-2-en-6-ones To a stirred solution of freshly distilled 6,6-dimethylfilvene (70.0 g, 74.9%, 0.49 mol) 14) and dichloroacetylchloride (106.6 g, 0.72 mol) in n-hexane (500 ml) was added dropwise Et 3 N (72.8 g, 0.72 mol) over a period of 1 h. The mixture was stirred for an additional 6 h and allowed to stand overnight. The reaction mixture was washed with H 2 O (3ϫ300 g).…”
Section: Methodsmentioning
confidence: 99%
“…Measurement: The 1 H-NMR spectra were measured with a JEOL GSX-270 spectrometer using tetramethylsilane as an internal standard. HR-MS spectrum was measured with JEOL JMS-HX-100.Synthesis of 7,7-Dichloro-4-isopropylidene-bicyclo[3.2.0]-hept-2-en-6-ones To a stirred solution of freshly distilled 6,6-dimethylfilvene (70.0 g, 74.9%, 0.49 mol) 14) and dichloroacetylchloride (106.6 g, 0.72 mol) in n-hexane (500 ml) was added dropwise Et 3 N (72.8 g, 0.72 mol) over a period of ICR Building 2F, …”
mentioning
confidence: 99%